A new species of Neoperla (Plecoptera: Perlidae) from Zhejiang Province of China - Chen, Zhi-Teng (Zootaxa, 2016)
The stonefly genus Neoperla Needham (1905) is primarily distributed in eastern North America, Tropical and Temperate Asia and central Africa, with at least 297 species known (Illies 1966, Zwick 1973, Stark & Gaufin 1976, DeWalt et al. 2016). Contributions to Chinese species of Neoperla were made by Chu (1929), Wu & Claassen (1934), Wu (1935, 1938, 1948, 1962, 1973), Yang & Yang (1992, 1995, 1998), Du (1999, 2000a, 2000b), Du et al. (1999, 2001), Du & Sivec (2004, 2005), Du & Wang (2005, 2007), Sivec & Zwick (1987), Li & Wang (2011), Li et al. (2011a, 2011b, 2012a, 2012b, 2013a, 2013b, 2014a, 2014b), Qin et al. (2013), Wang et al. (2013a, 2013b), Li & Zhang (2014), Kong et al. (2014), Wang et al. (2014), Chen & Du (2015). Herein, a new species of this genus is described from Taizhou, Zhejiang Province, of eastern coastal China.